2011
DOI: 10.1111/j.1741-2358.2010.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial edentulism and removable partial denture design in a dental school population: a survey in Greece

Abstract: A combination of the two major philosophies of RPD design (biomechanical and hygienic) was evident in the RPDs examined in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 15 publications
6
20
0
Order By: Relevance
“…These results are in agreement with other previous studies on the prevalence of partially edentulous arches . Charyeva et al found a majority of Kennedy Class III mandibular and maxillary arches and Niarchou found a majority of Kennedy Class I in both arches.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in agreement with other previous studies on the prevalence of partially edentulous arches . Charyeva et al found a majority of Kennedy Class III mandibular and maxillary arches and Niarchou found a majority of Kennedy Class I in both arches.…”
Section: Discussionsupporting
confidence: 91%
“…Pun et al found a nearly even number of maxillary versus mandibular RPDs, but the increased incidence of maxillary Class III (46.4%) compared to that found by Curtis et al (23%) may signal a lack of progress toward controlling dental disease. Also, the prevalence of mandibular RPDs could be related to a pattern of tooth loss and may lead to the many problems associated with mandibular complete dentures …”
Section: Discussionmentioning
confidence: 99%
“…In this study, there were more mandibular dentures (323) than maxillary (233). In addition, mandibular Class I was more prevalent mainly in patients between 40 and 60 years, which is in agreement with previous studies 4,5,12,16,19,25,[27][28][29] . The prevalence of mandibular RPDs is related to the pattern of teeth loss and related problems 27,29 .…”
Section: Maxillarysupporting
confidence: 93%
“…The frequency of various classes of partial edentulism and restoration types may reflect the aspects of the population on dental health prioritizations.6 Although several studies have been performed in different parts of the world on the prevalence of various classes of partial edentulism, classes of RPDs, and/or restoration types, 3,6,7,9,[11][12][13] there are no data available on both frequency of Kennedy classification and their treatment options in a subpopulation in Turkey. Therefore, the aim of this study was (i) to investigate the prevalence of partial edentulism classes, and (ii) to identify the prosthetic treatment options, such as overdenture, removable partial denture, fixed partial denture, implant or no restoration, for patients attending the Yeditepe University Faculty of Dentistry, Istanbul, Turkey.…”
Section: -10mentioning
confidence: 99%
“…5 There are many partial edentulism classification methods, however, Kennedy's classification is the most widely accepted method to classify the partially edentulous arches. 6,7 There are four main types in Kennedy classification; Class I (bilateral edentulous areas located posterior to the remaining natural teeth), Class II (a unilateral edentulous area located posterior to the remaining natural teeth), Class III (a unilateral edentulous area with natural teeth remaining both anterior and posterior to it), and Class IV (a single bilateral edentulous area located anterior to the remaining natural teeth).…”
Section: Introductionmentioning
confidence: 99%